2009
DOI: 10.1111/j.1467-629x.2009.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies and stock returns: Australian evidence

Abstract: Prior research has identified the existence of several cross-sectional patterns in equity returns, commonly referred to as effects. This paper tests for the existence of a number of well-known effects using data from the Australian equities market. Specifically, we investigate the size effect, book-to-market effect, earnings-to-price effect, cashflow-to-price effect, leverage effect and the liquidity effect. An additional aim of this paper is to investigate the capability of the Fama-French model in explaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 39 publications
11
29
0
Order By: Relevance
“…The difference in the results is mainly driven by firm size. This finding is consistent with prior Australian studies in which firm size is found to overpower the liquidity effect in explaining stock returns (Beedles, Dodd and Officer, 1988;Gharghori, Lee and Veeraraghavan, 2009). Furthermore, momentum is found to be insignificant or significantly negative in Models (1) to (7).…”
Section: Base Resultssupporting
confidence: 93%
“…The difference in the results is mainly driven by firm size. This finding is consistent with prior Australian studies in which firm size is found to overpower the liquidity effect in explaining stock returns (Beedles, Dodd and Officer, 1988;Gharghori, Lee and Veeraraghavan, 2009). Furthermore, momentum is found to be insignificant or significantly negative in Models (1) to (7).…”
Section: Base Resultssupporting
confidence: 93%
“…From this modest base, the body of work relating to the Australian BM effect has expanded rapidly in the last few years with the emergence of comprehensive financial accounting databases. While Gharghori et al (2009) report a significant value premium of 1.28% per month across 1993-2005, it does not survive risk adjustment via the FF3f model. Gharghori, Stryjkowski, and Veeraraghavan (2013) also report a value premium in raw returns over 1993-2009, but do not consider risk adjustment.…”
Section: Prior Researchmentioning
confidence: 71%
“…Gharghori et al (2009) document an earnings-to-price (EP) effect, where EP is defined as net profit after tax but before abnormals, scaled by market capitalisation. Partitioning the sample into firms with positive and negative EP, Gharghori et al (2009) found no relationship amongst the former partition, but a strong relationship between stock returns and the EP of the negative partition. This finding remains intact after adjusting for risk via the FF3f model.…”
Section: Prior Researchmentioning
confidence: 99%
“…We analyse the link between leverage and cross-section variation in returns, which is ignored in recent international asset pricing studies like that of Hou et al (2011). We provide further evidence in support of the impact of cash flows and earnings on returns, following Gharghori et al (2009b). Lastly, we find that some of the firm characteristic effects are sensitive to inclusion of the global financial crisis (GFC) period.…”
Section: Introductionmentioning
confidence: 79%